2013
DOI: 10.1002/jca.21257
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic plasma exchange: A technical and operational review

Abstract: Therapeutic plasma exchange (TPE) is an extracorporeal blood purification technique designed for the removal of large molecular weight substances. Examples of these substances include pathogenic autoantibodies, immune complexes, cryoglobulins, myeloma light chains, endotoxin and cholesterol containing lipoproteins. The basic premise of the treatment is that removal of these substances will allow for the reversal of the pathologic processes related to their presence. This review will cover the techniques for pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(138 citation statements)
references
References 57 publications
3
129
0
4
Order By: Relevance
“…45 The extent of plasma IgG reduction achieved in these preclinical investigations and in the clinical study 6 are comparable with the reduction (~ 50–60%) observed following a full course of repeated plasmapheresis procedures in humans, which is one of the current standards of care in autoimmune diseases. 52,53 This suggests that FcRn blockade may not only have clinical efficacy in autoimmune disease, but also that it could be more simply and rapidly administered, and may be more convenient and more specific in its mechanism of action than current treatments. Importantly, when rozanolixizumab dosing was stopped, plasma IgG concentrations returned to pre-dose levels, demonstrating that there was no lasting effect on FcRn.…”
Section: Resultsmentioning
confidence: 99%
“…45 The extent of plasma IgG reduction achieved in these preclinical investigations and in the clinical study 6 are comparable with the reduction (~ 50–60%) observed following a full course of repeated plasmapheresis procedures in humans, which is one of the current standards of care in autoimmune diseases. 52,53 This suggests that FcRn blockade may not only have clinical efficacy in autoimmune disease, but also that it could be more simply and rapidly administered, and may be more convenient and more specific in its mechanism of action than current treatments. Importantly, when rozanolixizumab dosing was stopped, plasma IgG concentrations returned to pre-dose levels, demonstrating that there was no lasting effect on FcRn.…”
Section: Resultsmentioning
confidence: 99%
“…TPE is expected to be a logical therapeutic option to consider in a disease condition in which the pathogenesis is linked to a specific toxic biologic substance that has a relatively high molecular mass (.15,000 D), a slow rate of formation, and distribution in the intravascular space (Table 1) (1). In contrast to hemodialysis or hemofiltration in which many substances with lower or middle molecular weights are targeted for removal, the target with TPE is typically a single constituent of plasma ( Figure 1) (2).…”
Section: Introductionmentioning
confidence: 99%
“…Our 20 year experience with the Cobe Spectra machine provided us with significant therapeutic outcomes lacking any technical problems. Spectra Optia is a new centrifugation system device by Caridian BCT Inc. 2009 which is being used in USA and Europe [9].…”
Section: Centrifugationmentioning
confidence: 99%